Thyrotoxicosis Induced Hypokalemic Periodic Paralysis in Organophosphorous Poisoning: A Case Report - Karki, Manoj; Rayamajhi, Bidhata; Raghubanshi, Prabesh; Kandel, Sanjog; Jha, Goody; Gautam, Narayan; Piryani, Rano Mal; Nepal, Monica (Journal of Universal College of Medical Sciences, 2022)
Organophosphate poisoning is a common emergency illness that requires medical attention because it causes a cholinergic state. As a result, atropine infusion is a sensible therapy option for patients. In our clinical setting, however, the unusual complication of thyrotoxicosis-induced hypokalemic periodic paralysis was reported.